SKIN EFFECTIVNESS OF FINE HYDRO-GEL CREAM CONTAINING BOTANICAL OIL COMPLEXES USING EMULSIFYING SYSTEM - In-Young Kim, Hyun-Dae Cho (International Journal of Research Science and Management, 2014)
This study was to get unique formulation of multi-functional activity for preparing hydro-gel cream using PIT emulsifying system. In order to develop the good safety, adsorption and multi-functions, we made a new formulation using phase inversion temperature (PIT) containing 4 botanical oils such as camellia japonica seed oil, macadamia integrifolia seed oil, limnanthes alba (meadowfoam) seed oil, argania spinosa kernel oil, 0.04wt% of adenosine and 2wt% of niacinamide. The fine botanical nutritive emulsion using PIT emulsifying method is easy absorbed into the stratum corneum because of fine droplet size. Appearance was high concentrated bluish liquid emulsion. PIT botanical oil complex was formed at around from 64 to 72 C. pH was 5.70.5. This formulation was very safety to protect on the skin, major droplet was mean 105nm containing 20wt% of PIT botanical complex. And also, there are fine wrinkle improvement and whitening effect containing. Skin in-vivo evaluations carried out the efficacy and functions of hydro-gel cream such as moisturizing effect, TEWL, fine wrinkle improvement and whitening activity. This hydro-gel cream is to find an optimum way to enhance the strengthening effect on skin barrier functions of cosmetic formulations.